The development of cities in Poland – the role of education - Orankiewicz, Agnieszka; Turała, Maciej (Potencjały rozwojowe miast – rola edukacji, 2019)
The discussion presented in this paper originates from the identification of three development potentials of cities: innovation-based, culture-based and education-based. The paper tackles the problem of determining the importance of primary, secondary and higher education for the development of cities. The main objective of the paper is to create a method for the measurement of education-based potential for development in Polish urban communes. To that end, five development factors encompassing 12 diagnostic variables were identified and a City Education Potential (CEP) index was constructed and its values calculated for 303 urban communes in Poland between 2013 and 2016. The CEP index was then used to: (1) prepare city rankings, (2) identify differences between small, medium-sized and large cities as well as (3) determine the significance of each diagnostic variable in each of the analysed size categories. The last part of the article also highlights the differences between regions in terms of the education-based potential of urban communes
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2019; vol. 63, nr 7, s. 271-285